Dispossessing vulnerable consumers: Derealization, desubjectification, and violence. (September 2018) - Varman, Rohit; Vijay, Devi
This article draws upon the work of Judith Butler to explain how violence is deployed against vulnerable consumers. It examines a site in which a commercial complex including a shopping mall is to be constructed in Ejipura, Bangalore (India), by displacing the poor from their slums. It offers insights into the mechanisms of violent dispossession that inhere liberal modes of governance of consumers. Moreover, this study attends to derealization that desubjectifies vulnerable consumers. It further helps to comprehend why violence remains in the zone of ellipsis without any popular revulsion against it.